An ultra-high-strength corrosion-resistant magnesium alloy plate and a preparation method thereof
Patent Information
- Application Number
- CN202611329437.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-27
AI Technical Summary
但现有镁合金耐腐蚀性能存在明显问题,主要因为镁具有较低的标准电极电位,因此镁基体易发生溶解现象
本发明通过直接添加Al、Zn、Mn、Ca及Zr等元素进行合金化处理,其中Al及Zn元素在Mg中具有较高的固溶度,可以起到较强的固溶强化作用,进而提升合金的机械强度。Mn元素在镁合金中可以净化熔体,提升合金的耐腐蚀性能。在镁合金中添加Ca元素可以降低熔体内的有害杂质,同时可以细化合金的晶粒尺寸,改善合金的力学性能。此外,Zr 具备优异的晶粒细化效果,通过细晶强化机制进一步提高合金强度。
Smart Images

Figure CN122979723A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of magnesium alloy material processing technology, specifically relating to a magnesium alloy sheet with both ultra-high strength and excellent corrosion resistance, and its preparation method. Background Technology
[0002] Magnesium alloys, as the lightest metallic structural materials currently available, have become the preferred choice for lightweighting in the automotive, rail transportation, aerospace, and electronic communications industries due to their low density, high specific strength and specific stiffness, as well as excellent shielding and seismic resistance. Currently, commonly used magnesium alloys are widely used due to their good room temperature forming capability and significant cost advantages, demonstrating broad commercial prospects and playing a crucial role in achieving structural lightweighting and energy conservation and emission reduction. However, existing magnesium alloys have significant problems with corrosion resistance, mainly because magnesium has a low standard electrode potential, making the magnesium matrix prone to dissolution. Furthermore, the oxide film on the surface of magnesium alloys cannot form a dense oxide film like that of aluminum alloys, leading to a significant reduction in corrosion resistance. Traditional magnesium alloys often achieve strength enhancement through multi-pass complex plastic deformation processes, which not only significantly increases manufacturing costs but also easily introduces microscopic defects that deteriorate the material's corrosion resistance. Therefore, there is an urgent need to develop a magnesium alloy sheet that does not rely on high rare earth content, has a simple manufacturing process, and possesses high strength and excellent corrosion resistance. Summary of the Invention
[0003] To solve the above-mentioned technical problems, this invention provides a high-strength and excellent corrosion-resistant magnesium alloy sheet and its preparation method. This invention uses alloying strengthening, plastic deformation and heat treatment strengthening to synergistically improve the strength and corrosion resistance of the alloy.
[0004] The technical solution adopted by this invention to achieve its objective is as follows: An ultra-high strength corrosion-resistant magnesium alloy plate uses the following alloying composition: Al 4.5-9.0%, Zn 0.2-2.5%, Mn 0.1-0.5%, Ca 0.1-0.4%, Zr 0.1-0.6%, with the balance being Mg.
[0005] Furthermore, the mass percentage of Al is preferably 6 to 8.5%.
[0006] Furthermore, the preferred mass percentage of Zn is 1 to 2%.
[0007] Furthermore, the mass percentage of Ca is preferably 0.15 to 0.3%.
[0008] Furthermore, the Zr mass percentage is preferably 0.15 to 0.3%.
[0009] Furthermore, the high-strength magnesium alloy has a tensile strength ≥350MPa, a yield strength ≥250MPa, and an elongation ≥10%.
[0010] Furthermore, the content of impurity elements such as Fe, Ni, and Cu that affect the corrosion resistance of magnesium alloys should all be less than 0.005%.
[0011] Furthermore, the magnesium alloy is melted using a vacuum induction melting method, which can effectively avoid the oxidation of the alloy.
[0012] The preparation method of the ultra-high strength corrosion-resistant magnesium alloy plate of the present invention includes the following steps: S1. Weigh the raw materials according to the following mass percentages: Al 4.5-9.0%, Zn 0.2-2.5%, Mn 0.1-0.5%, Ca 0.1-0.4%, Zr 0.1-0.6%, with the balance being Mg. Calculate the required mass of high-purity Mg ingots, high-purity Al ingots, high-purity Zn ingots, AlMn master alloy, MgCa master alloy, and MgZr master alloy, and prepare the materials accordingly. S2. Place the high-purity Mg ingot, high-purity Al ingot, high-purity Zn ingot, AlMn master alloy, MgCa master alloy and MgZr master alloy into a crucible; S3. Evacuate the furnace until the pressure inside drops below 10Pa, then fill it with 4N-grade high-purity argon gas, and maintain an argon protective atmosphere throughout the melting process; S4. Begin phased heating, first raising the temperature to 350-400℃ at a rate of 8-10℃ / min, then raising it to 700-750℃ at a rate of 3-5℃ / min, and holding it at that temperature for 1.5 hours. S5. During the heat preservation process, add electromagnetic stirring, and set the electromagnetic stirring frequency to 10-20 Hz; S6. After the heat preservation is completed, the melt is allowed to stand for 5 to 15 minutes before casting. After casting, the water cooling system is started to cool the melt, producing magnesium alloy ingots with a diameter of 200 to 250 mm. S7. The magnesium alloy ingot obtained in step S6 is subjected to turning, homogenization, forging and solution treatment in sequence to obtain ultra-high strength corrosion-resistant magnesium alloy sheet.
[0013] As a preferred embodiment, the high-purity Mg ingot is a 5N-grade high-purity magnesium ingot, the high-purity Al ingot is a 5N-grade high-purity Al ingot, and the high-purity Zn ingot is a 4.5N-grade high-purity Zn ingot. The purpose is to reduce impurity elements in the alloy, lower the risk of corrosion caused by impurities, and improve the alloy's corrosion resistance and microstructure uniformity from the compositional source.
[0014] As a preferred embodiment, the MgZr master alloy is prepared as follows: high-purity magnesium ingots are weighed according to the composition ratio of Mg-30Zr and placed in a crucible. The crucible is heated to 180-220°C under a high-purity argon protective atmosphere and held for 10-15 hours to dry out moisture. During smelting, the high-purity magnesium ingots are heated to 800-860°C, zirconium material is added in batches, and stirring is carried out continuously. After cooling, the MgZr master alloy is obtained.
[0015] As a preferred option, the stirring in step S5 is electromagnetic stirring, the stirring time is 50-60 minutes, and the electromagnetic stirring power can be adapted to the melt capacity as 10-30 kW. High-purity argon gas is introduced during the stirring process to reduce the risk of oxidation of the melt.
[0016] As a preferred option, the cooling rate of the water cooling treatment in step S6 is 80-110℃ / min. This cooling rate can effectively refine the grains, suppress the formation of coarse dendrites and element segregation in the alloy, and improve the uniformity of the alloy's structure and mechanical properties.
[0017] As a preferred embodiment, the purpose of the turning process in step S7 is to remove the oxide film layer generated on the outside of the alloy during the smelting process. The method is to use an alloy cutting tool to turn the outer circle of the ingot, removing a thickness of ≥2.5mm on one side.
[0018] As a preferred embodiment, the homogenization treatment temperature in step S7 is 300–450℃, and the treatment time is 2–4 hours; the forging treatment is as follows: the forging passes are 6, the reduction per pass is 15%–30%, after each forging pass, the forging billet is rotated 90° axially, then returned to the furnace and held at 350℃ before the next reduction is performed, the preheating temperature before forging is 320–380℃ and held for 6 hours, the final forging temperature is not lower than 260℃, and the forging is cooled by air cooling; the solution treatment method is: holding at 400–450℃ for 40–250 minutes.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention employs alloying treatment by directly adding elements such as Al, Zn, Mn, Ca, and Zr. Al and Zn have high solid solubility in Mg, providing strong solid solution strengthening and thus enhancing the alloy's mechanical strength. Mn purifies the melt in magnesium alloys, improving their corrosion resistance. Adding Ca to magnesium alloys reduces harmful impurities in the melt and refines the grain size, improving the alloy's mechanical properties. Furthermore, Zr exhibits excellent grain refinement, further enhancing the alloy's strength through a grain refinement strengthening mechanism.
[0020] This invention employs free forging technology to forge magnesium alloy ingots. By modifying the deformation process of free forging, sufficient deformation of the alloy can be achieved, improving the internal grain structure and further refining the grain size, thereby enhancing the alloy's strength. Magnesium alloy sheets produced using this invention's free forging process can be formed into large sizes, possessing the potential for large-scale application in various large-size component scenarios.
[0021] This invention employs a solution treatment method to dissolve the continuously distributed Mg-Al and Mg-Zn phases within the alloy into the α-Mg matrix. This disrupts the continuity of the second phase in the alloy, significantly reducing intergranular corrosion susceptibility and improving the alloy's localized corrosion resistance. Furthermore, the solution treatment temperature falls within the recrystallization temperature range of magnesium alloys, and the holding process effectively releases residual casting stress while mitigating the corrosion-promoting effects of crystal defects such as dislocations.
[0022] The smelting process of this invention uses a vacuum induction melting furnace, with high-purity argon gas introduced throughout the process for protection. This effectively inhibits the oxidation reactions of elements such as Mg, Al, and Zn, reduces the formation of oxides, and mitigates the impact of oxide inclusions on the corrosion resistance of the alloy. Attached Figure Description
[0023] Figure 1 It is a test report on the mechanical properties of magnesium alloy sheet.
[0024] Figure 2 It is a corrosion test report for magnesium alloy sheet.
[0025] Figure 3 This is the corrosion diagram of Example 1.
[0026] Figure 4 This is the corrosion diagram of Example 2.
[0027] Figure 5 This is the corrosion diagram of Example 3.
[0028] Figure 6 This is the corrosion diagram of Comparative Example 1. Detailed Implementation
[0029] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.
[0030] Raw material preparation: High-purity Mg ingots: purity 5N; High-purity Al ingots: purity 5N; High-purity Zn ingots: purity 4.5N; The AlMn master alloy was purchased from Lizhong Sitong Light Alloy Group Co., Ltd., and its grade was Al-10Mn. The MgCa master alloy was purchased from Shanxi Wenxi Yinguang Huasheng Magnesium Industry Co., Ltd., and its grade was Mg-20Ca. Preparation method of MgZr master alloy: Weigh high-purity magnesium ingots according to the composition ratio of Mg-30Zr and put them into a crucible. Heat the crucible to 180-220℃ under the protection of high-purity argon and hold for 10-15 hours. During melting, heat the high-purity magnesium ingots to 800-860℃, add zirconium material in batches and stir continuously. After cooling, MgZr master alloy is obtained.
[0031] High-purity argon: purity 4N.
[0032] Example 1
[0033] This embodiment provides an ultra-high strength corrosion-resistant magnesium alloy sheet and its preparation method, the specific steps of which are as follows: 1) The specific alloy composition of this embodiment is Mg-5Al-2Zn-0.2Ca-0.2Mn-0.3Zr, with the following specific mass content: Al: 5%, Zn: 2%, Ca: 0.2%, Mn: 0.2%, Zr: 0.3%, and the remainder being Mg; 2) Prepare the alloy according to the above composition. After the preparation is completed, put the high-purity Mg ingot, high-purity Al ingot, high-purity Zn ingot, AlMn master alloy, MgCa master alloy and MgZr master alloy into the crucible in sequence. 3) Evacuate the melting furnace to 2 Pa, then fill it with high-purity argon gas, and maintain an argon protective atmosphere throughout the melting process; 4) When starting the melting process, the temperature is first rapidly increased to 370℃ at a heating rate of 10℃ / min, and then slowly increased to 710℃ at a heating rate of 5℃ / min. The temperature is then held at 710℃ for 1.5 h. During the holding process, electromagnetic stirring is added (frequency 15Hz, stirring time 60min). High-purity argon gas is introduced during the stirring process to reduce the risk of oxidation of the melt. After the holding is completed, the melt is allowed to stand for 10 minutes before casting. Water cooling is used during the casting process (cooling rate 100℃ / min) to finally obtain corrosion-resistant magnesium alloy ingots. 5) The corrosion-resistant magnesium alloy is machined. The outer skin and riser of the corrosion-resistant magnesium alloy are machined. Then the machined corrosion-resistant magnesium alloy is homogenized and held at 350℃ for 2 hours, and then air-cooled to room temperature. 6) The homogenized corrosion-resistant magnesium alloy ingot is forged. Before forging, the ingot is preheated to 350°C and held for 6 hours. Then, it is forged in 6 passes with a reduction rate of 20% per pass. After each pass, the forging billet is rotated 90° axially and then returned to the furnace to be held at 350°C before the next pass. The final forging temperature is not lower than 270°C. After forging, it is air-cooled to room temperature. Then, the forged plate is solution-treated at 450°C for 200 minutes.
[0034] Example 2
[0035] This embodiment provides an ultra-high strength corrosion-resistant magnesium alloy sheet and its preparation method, the specific steps of which are as follows: 1) The specific alloy composition of this embodiment is Mg-7Al-1Zn-0.2Ca-0.3Mn-0.2Zr, with the following specific mass contents: Al: 7%, Zn: 1%, Ca: 0.2%, Mn: 0.3%, Zr: 0.2%, and the remainder being Mg; 2) Prepare the alloy according to the above composition. After the preparation is completed, put the high-purity Mg ingot, high-purity Al ingot, high-purity Zn ingot, Al-Mn master alloy, Mg-Ca master alloy and Mg-Zr master alloy into the crucible in sequence. 3) Evacuate the melting furnace to 3Pa, then fill it with high-purity argon gas, and maintain an argon protective atmosphere throughout the melting process; 4) When starting the melting process, the temperature is first rapidly increased to 350℃ at a heating rate of 10℃ / min, and then slowly increased to 720℃ at a heating rate of 5℃ / min. The temperature is then held at 720℃ for 1.5 h. During the holding process, electromagnetic stirring is added (frequency 15Hz, stirring time 60 min). High-purity argon gas is introduced during the stirring process to reduce the risk of oxidation of the melt. After the holding is completed, the melt is allowed to stand for 10 min before casting. Water cooling is used during the casting process (cooling rate 100℃ / min) to finally obtain corrosion-resistant magnesium alloy ingots. 5) The corrosion-resistant magnesium alloy ingot is machined to remove the outer skin and riser. Then the machined corrosion-resistant magnesium alloy ingot is subjected to homogenization annealing treatment, held at 380℃ for 3 hours, and then air-cooled to room temperature. 6) The corrosion-resistant magnesium alloy ingots after homogenization treatment are subjected to free forging. Before forging, the ingots are preheated to 350°C and held for 6 hours. Then, 6 forging passes are performed, with a reduction rate of 20% for each pass. After each forging pass, the billet is rotated 90° axially and then returned to the furnace to be held at 350°C before the next pass is performed. The final forging temperature is not lower than 270°C. After forging, the billet is air-cooled to room temperature. Then, the forged plate is subjected to solution treatment at a temperature of 440°C for 190 minutes.
[0036] Example 3
[0037] This embodiment provides an ultra-high strength corrosion-resistant magnesium alloy sheet and its preparation method, the specific steps of which are as follows: 1) The specific alloy composition in this embodiment is Mg-8.5Al-1Zn-0.3Ca-0.4Mn-0.3Zr, with the following specific mass contents: Al: 8.5%, Zn: 1%, Ca: 0.3%, Mn: 0.4%, Zr: 0.3%, and the remainder being Mg; 2) Prepare the alloy according to the above composition. After the preparation is completed, put the high-purity Mg ingot (N5 grade), high-purity Al ingot, high-purity Zn ingot, Al-Mn master alloy, Mg-Ca master alloy and Mg-Zr master alloy into the crucible in sequence. 3) Evacuate the melting furnace to 3Pa, then fill it with high-purity argon gas, and maintain an argon protective atmosphere throughout the melting process; 4) When starting the melting process, the temperature is first rapidly increased to 370℃ at a heating rate of 10℃ / min, and then slowly increased to 730℃ at a heating rate of 5℃ / min. The temperature is then held at 730℃ for 1.5 h. During the holding process, electromagnetic stirring is added (frequency 15Hz, stirring time 60 min). High-purity argon gas is introduced during the stirring process to reduce the risk of oxidation of the melt. After the holding is completed, the melt is allowed to stand for 12 min before casting. Water cooling is used during the casting process (cooling rate 100℃ / min) to finally obtain corrosion-resistant magnesium alloy ingots. 5) The corrosion-resistant magnesium alloy ingot is machined to remove the outer skin and riser. Then the machined corrosion-resistant magnesium alloy ingot is subjected to homogenization annealing treatment, held at 350℃ for 3 hours, and then air-cooled to room temperature. 6) The corrosion-resistant magnesium alloy ingots after homogenization treatment are subjected to free forging. Before forging, the ingots are preheated to 350°C and held for 6 hours. Then, 6 forging passes are performed, with a reduction rate of 20% for each pass. After each pass, the billet is rotated 90° axially and then returned to the furnace to be held at 350°C before the next pass is performed. The final forging temperature is not lower than 280°C. After forging, the billet is air-cooled to room temperature. Then, the forged plate is subjected to solution treatment at 450°C for 120 minutes.
[0038] Performance testing The magnesium alloy sheets prepared in Examples 1-3 were subjected to room temperature tensile property tests and corrosion resistance tests. Tensile property tests were conducted according to GB / T 228.1-2010 standard. The specimens were processed into cylindrical tensile specimens with a gauge length of 50 mm and a diameter of 25 mm, and the tensile rate was 1 mm / min. Corrosion resistance tests were conducted according to GB 10124-88 standard. The experimental method was the full immersion test, using a 3.5 wt% NaCl solution as the corrosive solution. The test temperature was room temperature, the sample size was 50 × 50 × 3 mm, and the test duration was 7 days.
[0039] Table 1 Mechanical properties and corrosion resistance of magnesium alloy plates in Examples 1-3
[0040] As shown in Table 1, the magnesium alloy sheets prepared in Examples 1-3 all have tensile strengths exceeding 350 MPa, yield strengths exceeding 260 MPa, elongations exceeding 10%, and weight loss rates not exceeding 0.24 mg / cm³. 2 / day, exhibiting excellent high strength and good corrosion resistance.
[0041] Comparative Example 1 A standard commercial AZ31 magnesium alloy sheet (composition: Mg-3Al-1Zn-0.3Mn) was used as a comparative example, and its mechanical properties and corrosion resistance were tested under the same test conditions. The test results are shown in Table 2.
[0042] Table 2 Performance Comparison between Comparative Examples and Embodiments of the Present Invention
[0043] As shown in Table 2, compared with conventional commercial AZ31 magnesium alloy, the magnesium alloy sheet prepared in Example 1 of this invention exhibits an increase in tensile strength of approximately 21.6%, a yield strength of approximately 24.8%, and a weight loss rate of 85.1%, demonstrating significantly superior overall performance compared to existing commercial magnesium alloys. These results indicate that this invention, through rational alloying design and optimized vacuum melting, electromagnetic stirring, water-cooled casting, free forging, and solution treatment processes, effectively refines the grain structure, optimizes the second-phase distribution, and reduces the tendency for galvanic corrosion, thereby achieving a synergistic improvement in both strength and toughness, as well as corrosion resistance.
[0044] Finally, it should be noted that the above-described embodiments are merely specific implementations of the present invention, used to illustrate the technical solutions of the present invention, and not to limit them. The scope of protection of the present invention is not limited thereto. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that any person skilled in the art can still modify or easily conceive of changes to the technical solutions described in the foregoing embodiments within the scope of the technology disclosed in the present invention, or make equivalent substitutions for some of the technical features; and these modifications, changes, or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be covered within the scope of protection of the present invention.
Claims
1. A high-strength, corrosion-resistant magnesium alloy sheet, characterized in that, By mass percentage, it includes Al 4.5–9.0%, Zn 0.2–2.5%, Mn 0.1–0.5%, Ca 0.1–0.4%, Zr 0.1–0.6%, with the balance being Mg.
2. The ultra-high strength corrosion-resistant magnesium alloy sheet according to claim 1, characterized in that, The mass percentage of Al is 6–8.5%; the mass percentage of Zn is 1–2%; the mass percentage of Ca is 0.15–0.3%; and the mass percentage of Zr is 0.15–0.3%.
3. The ultra-high strength corrosion-resistant magnesium alloy sheet according to claim 1, characterized in that, It also includes impurities, with a total impurity content of <100ppm, and the content of Fe, Ni and Cu elements in the impurities is less than 0.005%.
4. The ultra-high strength corrosion-resistant magnesium alloy sheet according to claim 1, characterized in that, The ultra-high strength corrosion-resistant magnesium alloy sheet has a tensile strength ≥350MPa, a yield strength ≥250MPa, and an elongation ≥10%.
5. The method for preparing an ultra-high strength corrosion-resistant magnesium alloy sheet as described in claim 1, characterized in that, Includes the following steps: S1. Weigh the raw materials according to the following mass percentages: Al 4.5-9.0%, Zn 0.2-2.5%, Mn 0.1-0.5%, Ca 0.1-0.4%, Zr 0.1-0.6%, with the balance being Mg. Calculate the required mass of high-purity Mg ingots, high-purity Al ingots, high-purity Zn ingots, AlMn master alloy, MgCa master alloy, and MgZr master alloy, and prepare the materials accordingly. S2. Place the high-purity Mg ingot, high-purity Al ingot, high-purity Zn ingot, AlMn master alloy, MgCa master alloy and MgZr master alloy into a crucible; S3. Evacuate the furnace until the pressure inside drops below 10Pa, then fill it with high-purity argon gas. Maintain an argon protective atmosphere throughout the melting process. S4. Begin phased heating, first raising the temperature to 350-400℃ at a rate of 8-10℃ / min, then raising it to 700-750℃ at a rate of 3-5℃ / min, and holding it at that temperature for 1.5 hours. S5. During the heat preservation process, add electromagnetic stirring, and set the electromagnetic stirring frequency to 10-20 Hz; S6. After the heat preservation is completed, the melt is allowed to stand for 5 to 15 minutes before casting. After casting, it is water-cooled to produce magnesium alloy ingots with a diameter of 200 to 250 mm. S7. The magnesium alloy ingot obtained in step S6 is subjected to turning, homogenization, forging and solution treatment in sequence to obtain ultra-high strength corrosion-resistant magnesium alloy sheet.
6. The method for preparing an ultra-high strength corrosion-resistant magnesium alloy sheet according to claim 5, characterized in that, The high-purity Mg ingot is a 5N grade high-purity magnesium ingot, the high-purity Al ingot is a 5N grade high-purity Al ingot, and the high-purity Zn ingot is a 4.5N grade high-purity Zn ingot.
7. The method for preparing an ultra-high strength corrosion-resistant magnesium alloy sheet according to claim 5, characterized in that, The MgZr master alloy is prepared as follows: high-purity magnesium ingots are weighed according to the composition ratio of Mg-30Zr and placed in a crucible. The temperature is raised to 180-220°C under the protection of high-purity argon and held for 10-15 hours. During melting, the high-purity magnesium ingots are heated to 800-860°C, zirconium material is added in batches, and stirring is carried out continuously. After cooling, the MgZr master alloy is obtained.
8. The method for preparing an ultra-high strength corrosion-resistant magnesium alloy sheet according to claim 5, characterized in that, In step S5, the electromagnetic stirring time is 50-60 minutes, and the electromagnetic stirring power is adapted to the melt capacity as 10-30 kW. High-purity argon gas is introduced for protection during the stirring process.
9. The method for preparing an ultra-high strength corrosion-resistant magnesium alloy sheet according to claim 5, characterized in that, The cooling rate of the water cooling process in step S6 is 80-110℃ / min.
10. The method for preparing an ultra-high strength corrosion-resistant magnesium alloy plate according to claim 5, characterized in that, The homogenization treatment temperature in step S7 is 300-450℃, and the treatment time is 2-4 hours. The forging treatment is as follows: there are 6 forging passes, and the reduction per pass is 15%-30%. After each forging pass, the billet is rotated 90° axially, then returned to the furnace and held at 350℃ before the next reduction. The preheating temperature before forging is 320-380℃ and held for 6 hours. The final forging temperature is not lower than 260℃. After forging, it is cooled by air cooling. The solution treatment method is: holding at 400-450℃ for 40-250 minutes.